Automation and control in electric power systems: a review of intelligent system applications - Torres, Germano Lambert (Revista Ciências Exatas, 2008)
There is a permanent demand for new application and simulation software, required for different purposes such as research, planning and power system operation. This paper presents an overview of some developments of the author for Brazilian power system industries. These developments are currently in operation and usually they are based on intelligent hybrid systems.